Barriers to Teaching Arabic Speech: A Case Study for Seventh Grade Students in Public Middle School Gresik: عوائق تعليم مهارة الكلام باللغة العربية: دراسة حالة لطلاب الصف السابع في المدرسة المتوسطة الحكومية كرسيك - Maghfiroh, Lailatun; Dimyathi, Muhammad Afifudin (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
Arabic language learning in Indonesia must be resolved immediately because it always faces linguistic and non-linguistic problems. Non-linguistic problems include learning motivation, media, model, allocation, and learning environment. Linguistic problems include linguistic problems such as phonetics, morphology, and syntax. The age of the students and the learning environment determine many language learning problems. This article reviews the obstacles faced by seventh grade students of MTs Negeri Gresik when learning to speak Arabic. This paper uses descriptive analysis through interviews, direct observation, and document collection. After data collection and analysis results identified two main factors that cause this difficulty, one of which is factors outside the Arabic language itself. The results show that similar problems are also common in other madrasahs. Although focused on one school, this study makes an important contribution in understanding the Arabic speaking difficulties that are often experienced by grade VII students, especially in a madrasah environment. This paper can be the basis for Arabic teachers to design more effective and innovative learning strategies to overcome the problems faced by students. In addition, this research contributes to the curriculum development team, especially in terms of determining relevant learning materials and developing learning methods that better accommodate the needs of students. And finally, the results of this analysis can be a reference for future research that wants to explore similar issues in other schools